Tree Sap Induced Corneal and Lens Crystals - Nadeem, Sana (Pakistan Journal of Ophthalmology, 2020)
This is a peculiar case of localized, silvery, iridescent crystal deposition in the cornea and lens, discovered twenty seven years after injury with an overhanging tree branch with sap exposure. The corneal tear at the time of injury was self sealing and there was also associated lens trauma, both managed conservatively on an inpatient basis, and leading subsequently to a corneal scar and localized cortical cataract, respectively, both demonstrating fine, silver, interspersed crystals. This is the first case to be reported in the world, of corneal crystal deposition in conjunction with lenticular crystals as a result of a tree branch injury.